Diversity of rhizobia in Phranakhon si ayutthaya province - Maruekarajtinplaeng, Sujidkanlaya (Asia-Pacific Journal of Science and Technology, 2017)
The purpose ofthis research was to isolate and studybiodiversity of rhizobia from sixteen districts in Phranakornsi Ayutthaya province. The result of bacterial isolation showed 160 isolates. The 25 from 160 isolates were randomly selected to study physiologicalon Yeast Extract Mannitol Agar (YMA) supplemented with 0.25 ?gml-1congored. They were identifidin 2 groups: fastgrowth and slowergrowth. Base donacid-base production on YMA with bromothymolblue as an indicator and incubated at 30?C, the results couldbe classifidin 3 types. Type Isoil Rhizobia produced only acidafter 10-day incubation while type II secreted alkaline metabolize 5-day incubation and subsequently produced acid metabolize after continuous incubation for another 5 days. Type III released only alkaline throughout10-day incubation. Furthermore, the effect ofsalinity on bacterial growth was studied with the variation of NaCl concentration. Most soil Rhizobia could be presented on the medium sup - plementedwith low concentrationofNaCl. Inaddition, the resistant reaction of antibiotic was showed thatmost isolate swereabletoresist Chloramphenicol (30?g).Comparative sequence analysis of the 25 isolates according to the16SrDNA sequencing revealed that 25 isolates were classifidas Bradyrhizobium japonicum, Bradyrhizobium yuanmingense, Bradyrhizobium elkaniiand Sinorhizobium saheli